A brief acceptance and commitment intervention for work‐related stress and burnout amongst frontline homelessness staff: A single case experimental design series. (25th March 2021) - Reeve, Andy; Moghaddam, Nima; Tickle, Anna; Young, Dave
Abstract: Purpose: Recent intervention research for burnout amongst those working in health and social care contexts has found acceptance and commitment therapy (ACT) interventions to be of use but has provided less clarity on the role of psychological flexibility (a key ACT construct). This study further evaluated the usefulness of ACT for burnout and work‐engagement and assessed the role of psychological flexibility in contributing to therapeutic change. Procedure: A nonconcurrent multiple‐baseline across‐participants single‐case experimental design was used. Four participants were recruited from a homelessness organization in the East Midlands, England. The ACT‐intervention was split into three modules to reflect the three aspects of the ACT triflex, and the sequence of delivery was randomized for each participant in order to test the relationship between these aspects. Findings: Support was found for the ACT intervention reducing exhaustion and increasing work‐engagement. Psychological Flexibility increased in all participants and was temporally related to increases in other outcome variables in some instances. Delivery of the intervention focussed on any given aspect of the ACT triflex could increase different domains of psychological flexibility. Implications: This study adds to the growing body of research in favour of ACT interventions for burnout and adds to the understanding of psychological flexibility as a mediating variable.